PENGEMBANGAN PENGERING BEKU PEMBEKUAN VAKUM DENGAN PEMANASAN KONDENSER - Rahmat Subarkah1; Nasruddin _; Belyamin _ (Politeknik Negeri Jakarta, 2011)
Every year, West Kalimantan exports fresh aloevera abroad and at the same time the domestic industry imports aloevera powder produced by freeze drying process. If the freeze drying machine can be produced domestically, the aloevera product that became the mainstay of West Kalimantan can be processed in Indonesia. To achieve this long-term goal, a study that could result in freeze drying machine that can produce aloevera powder efficiently is needed. The process of designing, manufacturing and testing of vacuum freeze drying machine with condenser waste heat conducted at the Refrigeration Laboratory of Department of Mechanical Engineering UI. Vacuum freeze drying machine is designed and fabricated consisting of Chamber (there are containers placed material, the upper and lower heater) and Evaporator (cooling systems). This research has resulted a machine of freezing vacuum freeze dryers with heating condenser, working pressure -1 up to 3 millibars, the chamber temperature to minus or below 0 ºC, condenser temperature reaches 35 º C. In the drying process does not use a heating condenser then sublimation process completion time for 13 hours and obtained LOD values of ± 98.6%, while in the drying process that uses a heating condenser, it is time to 6.5 to 7 hours and obtained LOD values of ± 95 , 6%. Keywords : aloevera, freeze drying, vacuum freeze ABSTRAK Setiap tahun Kalimantan Barat mengekspor lidah buaya segar ke luar negeri dan pada saat yang sama industri dalam negeri mengimpor serbuk lidah buaya yang dihasilkan dengan proses pengeringan beku. Jika dapat dihasilkan mesin pengering beku di dalam negeri, maka lidah buaya yang menjadi produk andalan Kalimantan Barat dapat diproses di dalam negeri. Untuk mencapai tujuan jangka panjang ini maka diperlukan suatu penelitian yang dapat menghasilkan mesin pengering beku yang dapat memproduksi serbuk lidah buaya dengan efisien. Proses perancangan, pembuatan dan pengujian mesin pengeringan beku vakum dengan panas buang kondenser dilakukan di Lab Refrigerasi Departemen Teknik Mesin UI. Mesin pengeringan beku vakum yang dirancang dan dibuat terdiri dari Ruang Uji (terdapat wadah meletakkan material, pemanas atas dan bawah) dan Ruang Evaporator (Sistem refrigerasi). Penelitian ini menghasilkan alat pengering beku pembekuan vakum dengan pemanasan kondensor dengan tekanan kerja -1 hingga 3 milibar, suhu ruang chamber mencapai minus atau dibawah 0ºC, suhu kondensor mencapai 35ºC. Pada proses pengeringan yang tidak menggunakan pemanasan kondensor maka waktu terselesaikannya proses sublimasi selama 13 jam dan didapatkan nilai LOD sebesar ± 98,6 % sedangkan pada proses pengeringan yang menggunakan pemanasan condenser maka waktunya menjadi 6,5 hingga 7 jam dan didapatkan nilai LOD sebesar ± 95,6 %. Katakunci: aloevera, freeze drying, vacuum freeze